Effect of environmental conditions on the concentration of tear inflammatory mediators during contact lens wear - Martín-Montañez, Vicente (2016)
Purpose: To analyze the influence of environmental conditions on the concentrations of tear inflammatory mediators during contact lens (CL) wear. Methods: Fifty-four CL wearers completed 4 visits combining the bilateral use of omafilcon A or comfilcon A CL and a 90-minute exposure to 2 environmental conditions: standard [50% relative humidity (RH), 23°C, 930 mb] or adverse (5% RH, localized air flow, 23°C, 750 mb). Four microliters of tears was collected by capillarity from each subject. Changes in concentration of epidermal growth factor (EGF); interleukin (IL)-1 receptor antagonist, IL-1b, IL-2, IL-4, IL-6, and IL-8; tumor necrosis factor (TNF) a; monocyte chemoattractant protein-1; and matrix metalloproteinase (MMP)-9 were analyzed. The effects of the environment, CL type, and symptoms were evaluated using a 3-way mixed analysis of variance with repeated measures. Results: Under the standard condition, EGF significantly increased [0.36; 95% confidence interval (CI), 0.08 to 0.64], and IL-1b (20.48; 95% CI, 20.84 to 20.12) and IL-2 (20.48; 95% CI, 20.87 to 20.09) significantly decreased. Under the adverse condition, IL-6 significantly increased (0.35; 95% CI, 0.09 to 0.62). Comparing conditions, EGF change was significantly lower (P = 0.02) and IL-1b, IL-2, IL-6, and TNF-a changes were significantly higher (P # 0.04) under the adverse condition. Additionally, IL-1b significantly decreased with comfilcon A (20.51; 95% CI, 20.88 to 20.15), being significantly lower (P = 0.01) than the change with omafilcon A (0.06; 95% CI, 20.23 to 0.35). Conclusions: The secretion of several tear inflammatory mediators during CL wear differs depending on the environmental conditions and the CL type used. These outcomes might help to understand the effect of the environment and CL materials on the ocular surface of CL wearers